Association mapping of yield and yield-related traits under reproductive stage drought stress in rice (Oryza sativa L.) - Swamy, B.P.Mallikarjuna; Shamsudin, Noraziyah Abd Aziz; Rahman, Site Noorzuraini Abd; Mauleon, Ramil; Ratnam, Wickneswari; Sta. Cruz, Ma.Teressa; Kumar, Arvind (Springer, 2017)
# Background